Randomised, double-blind, placebo-controlled trial of EPs 7630 in adults with COPD - Matthys, Heinrich; Pliskevich, Dina A.; Bondarchuk, Oleksandr M.; Malek, Fathi A.; Tribanek, Michael; Kieser, Meinhard (Respiratory medicine, 2013)
Background - Preventing and managing exacerbations is one major component in COPD treatment. We investigated whether EPs 7630, a herbal drug preparation from the roots of Pelargonium sidoides, could prolong time to acute exacerbation in patients with COPD stage II/III. - Methods - In this randomised, double-blind, placebo-controlled clinical trial, patients were randomly allocated to oral 24-week add-on therapy with 3 × 30 drops/day EPs 7630 (n = 99) or placebo (n = 101) to a standardised baseline-treatment. Primary endpoint was time to first exacerbation of COPD. Secondary endpoints were number of exacerbations, consumption of antibiotics, quality of life, patient satisfaction, inability to work, and tolerability. - Results - Median time to exacerbation was significantly prolonged with EPs 7630 compared to placebo (57 versus 43 days, Kaplan-Maier-estimate; p = 0.005, one-sided centre-stratified log-rank test). The superiority of EPs 7630 was also confirmed in secondary endpoints, e.g., fewer exacerbations, less patients with antibiotic use, improved quality of life, higher patient satisfaction, and less days of inability to work. The incidence of minor gastrointestinal adverse events was higher in the EPs 7630 group. - Conclusions - The results demonstrate a statistically significant and clinically relevant superiority of add-on therapy with EPs 7630 over placebo and a good long-term tolerability in the treatment of moderate to severe COPD. EPs 7630 prolonged time to exacerbations and reduced exacerbation frequency and antibiotic use. Trial Registration No.: ISRCTN01681733.
Gesehen am 25.06.2021